Development and Investigation on Mechanical Properties of Pongamia Oil-Cake/UHMWPE filled Basalt Epoxy composites. (2018) - Kumar R. Tavadi, Ashok; Mohan, N.; Kumar K Chavan, Sandeep
Abstract: In this Investigation, the effect of different percentage (0wt% to 9wt %) of UHMWPE and (3wt % to 6 wt%) Pongamia oil Cake filled basalt epoxy composites on the tensile, impact and hardness properties of composite was investigated. The specimens were prepared by using vacuum assisted resin transfer molding technique. Tensile, impact and Hardness test were carried out as per standards (ASTM). The micro fractured analysis of all the samples were examined by using scanning electron microscope. The experimental results showed significant improvement in both tensile, modules by the incorporation of Pongamia oil Cake into the basalt/epoxy composite. The result shows that increase of 11% tensile strength and 19% modulus in 6wt % Pongamia oil cake filled composites as compared to neat basalt epoxy composite and also results revealed that the addition of 3w%t UHMWPE to Basalt epoxy shows better tensile strength and Hardness value compared to 6wt%, 9wt% UHMWPE as filler. The improved Performance of Pongamia oil-Cake /basalt epoxy composites is a characteristic quality of distribution of protein ash and oil particles in the epoxy matrix contributing more outer area for energetic adhesion and stress displacement between matrix and fibre surface.